REVOLUSI DIGITAL: TRANSFORMASI TEKNOLOGI INFORMASI DALAM PENDIDIKAN ISLAM MODERN - Ramadhona, Rossa; Harto, Kasinyo; Amilda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education in Indonesia is a strategic sector that continues to experience significant changes, but still faces major challenges such as gaps in access and disparities in quality between regions, especially in remote areas that are still lagging behind in terms of infrastructure and teaching staff; in the midst of these conditions, Islamic education through madrasas and Islamic boarding schools continues to play an important role in shaping the character and spirituality of the younger generation, and has transformed by integrating the national curriculum to increase its competitiveness; facing the modern era that is digital and rapidly changing, Islamic education is required to innovate in learning methods that combine Islamic values ​​with technological adaptation in order to remain relevant and able to produce graduates who are religious and competent in various fields of life. The research method is qualitative. Digital transformation in Islamic education brings major changes with the use of information technology that expands access to learning, enriches teaching methods, and encourages global collaboration, but is accompanied by challenges such as gaps in access to technology, limited digital competence, and the need for accurate supervision of religious content; with the right strategies such as strengthening infrastructure, digital training for educators, developing quality content, and policy support, Islamic education can develop more inclusively, relevantly, and effectively in the digital era without sacrificing Islamic values.